Deskripsi Pemahaman Konsep Himpunan Fuzzy Mahasiswa Melalui Pembelajaran PMRI - Intan Buhati Asfyra; Ja’faruddin Ja’faruddin (Universitas Muhammadiyah Palembang, 2026)
This study aims to examine students’ understanding of fuzzy set concepts through the implementation of Indonesian Realistic Mathematics Education (PMRI). The study employed a descriptive qualitative approach involving nine students from the Mathematics Education Study Program at Universitas Negeri Makassar. Data were collected through tests, interviews, observations, and documentation, and analyzed using an interactive analysis model. The results indicate that students’ conceptual understanding can be categorized into three levels: high, medium, and low. Students in the high category have reached the stage of formal mathematization, as demonstrated by their ability to construct membership functions systematically and apply fuzzy operations appropriately. Meanwhile, students in the medium category exhibit an intuitive understanding but lack consistency in developing mathematical models. In contrast, students in the low category tend to think in a crisp manner and have not yet understood the concept of membership degrees conceptually. The mathematization process begins with understanding the context and progresses toward the formation of mathematical models, although not all students reach the formal stage. PMRI-based learning is proven to help students understand fuzzy concepts through realistic contexts and discussions. However, its effectiveness is influenced by individual abilities, indicating the need for more intensive guidance.